2015
DOI: 10.1016/j.redox.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Ovotoxicants 4-vinylcyclohexene 1,2-monoepoxide and 4-vinylcyclohexene diepoxide disrupt redox status and modify different electrophile sensitive target enzymes and genes in Drosophila melanogaster

Abstract: The compounds 4-vinylcyclohexene 1,2-monoepoxide (VCM) and 4-Vinylcyclohexene diepoxide (VCD) are the two downstream metabolites of 4-vinylcyclohexene (VCH), an ovotoxic agent in mammals. In addition, VCM and VCD may be found as by-products of VCH oxidation in the environment. Recently, we reported the involvement of oxidative stress in the toxicity of VCH in Drosophila melanogaster. However, it was not possible to determine the individual contributions of VCM and VCD in VCH toxicity. Hence, we investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 68 publications
(73 reference statements)
5
50
0
Order By: Relevance
“…The two main lines of defense against oxidative stress are endogenous antioxidant molecules (Abolaji, Kamdem, & Lugokenski, 2015) and repair enzymes that remove or repair oxidatively damaged macromolecules. Also, living organisms can withstand damages caused by oxidative stress in reaction to pro‐oxidants through the process of adaptive response (Crawford & Davies, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two main lines of defense against oxidative stress are endogenous antioxidant molecules (Abolaji, Kamdem, & Lugokenski, 2015) and repair enzymes that remove or repair oxidatively damaged macromolecules. Also, living organisms can withstand damages caused by oxidative stress in reaction to pro‐oxidants through the process of adaptive response (Crawford & Davies, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) are harmful molecules, capable of inducing oxidative damage in amino acids, proteins, lipids, and DNA components of tissues at higher levels (Sharma, 2015;Valko, Rhodes, Moncol, Izakovic, & Mazur, 2006). The two main lines of defense against oxidative stress are endogenous antioxidant molecules (Abolaji, Kamdem, & Lugokenski, 2015) and repair enzymes that remove or repair oxidatively damaged macromolecules. Also, living organisms can withstand damages caused by oxidative stress in reaction to pro-oxidants through the process of adaptive response (Crawford & Davies, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The fine balance between reactive oxygen species (ROS) production and scavenging by endogenous antioxidants are of utmost importance for testicular function. Interestingly, elevated levels of reactive oxygen and nitrogen species production with concomitant disruption of the antioxidant system in Drosophila melanogaster exposed to VCH and VCD have been reported by our research group [12,13]. In addition, we recently reported that, exposure to VCD-induced oxidative stress, resulting in hepatic and renal oxidative damage in male and female rats [10].…”
Section: Introductionmentioning
confidence: 70%
“…Male and female wild type Drosophila melanogaster (Harwich strains) were acquired from the Drug Metabolism and Molecular Toxicology Research Laboratory, Department of Biochemistry, University of Ibadan, Ibadan, Nigeria. The culture and feeding medium, which was largely cornmeal based, was hygienically adopted from protocols reported by Abolaji et al (Abolaji et al, 2015). The flies were maintained under a cool and regulated temperature (23 ± 3°C), 60% humidity and natural day/night cycles in the Neurophytotherapy Lab (NPTL), Department of Anatomy, Olabisi Onabanjo University, Sagamu, Nigeria.…”
Section: Acquisition and Breeding Of Fliesmentioning
confidence: 99%